Let’s Cook: An Augmented Reality System Towards Developing Cooking Skills for Children with Cognitive Impairments - Papadaki, Eleni; Ntoa, Stavroula; Adami, Ilia; Stephanidis, Constantine (Smart Objects and Technologies for Social Good, 2018)
Although activities of daily living are often difficult for individuals with cognitive impairments, their autonomy and independence can be fostered through interactive technologies. The use of traditional computer interfaces has however proved to be difficult for these users, bringing to the surface the need for novel interaction methods. This paper proposes Let’s Cook, an innovative Augmented Reality game, designed to teach children with cognitive impairments how to prepare simple meals, following a playful approach. Let’s Cook supports multimodal interaction techniques utilizing tangible objects on a table-top surface, as well as multimedia output. Additionally, it can be personalized to accommodate the diverse needs of children with cognitive impairments by employing individual user profiling. The system is currently installed in the kitchen of the Rehabilitation Centre for Children with Disabilities in Heraklion, Crete where it was evaluated by the students.